OIL PALM FRESH FRUITS (FFB) RENDEMENT IN THE EAST REGION OF ACEH PROVINCE - Romano, Romano; Ramayana, Ramayana; Putri Lestari, Pratiwi; Tambarta Kembaren, Emmia; Bagio, Bagio (RADJA PUBLIKA, 2022)
The purpose of this researchanalyzed the determinants of oil palm FFB yield on each character of coastal land and mineral land in the eastern region of Aceh Province based on variety and harvest fraction. Research has been carried out using survey methods and experiments in laboratories with36 samples of palm FFB were taken for three parts which would be used as a repeat in determining the yield of CPO and fatty acids from the palm FFB. The results showed that the yield of CPO was determined by various factors, including: suitability for oil palm development areas, types (Dura and Tenera), and maturity fraction. In Dura palms with thinner mesocarf, the yield of CPO is lower than Tenera. The FFB maturity fraction at harvest greatly determines the yield of CPO and the quality of the oil. The best yield and quality of CPO on the F2 and F3 maturity fractions. The KPO yield of Dura palm is higher than that of Tenera, so it is more profitable to plant the Tenera type. Therefore it is necessary to evaluate the use of dura and tenera seeds for the development of smallholder oil palm in the east coast of Aceh to obtain the quantity and quality of CPO